(untitled) (Research, Society and Development, 2020)
Mental calculation is that, exact or approximate, that is done mentally, or with notes to support the reasoning, which does not depend exclusively on the use of algorithms and counting. Although it allows a better understanding of mathematics and influences the future of children, this tool has not been used to its full potential. For its use to happen, teachers must be aware of its importance in the teaching-learning process and know how to use it. This study, characterized as an explanatory research of qualitative character, aims to study the main strategies of mental calculation described in the literature, in the texts of Thompson (1999) and Butterwoth (2005), to analyze the previous knowledge necessary for each one of them and, finally, develop suggestions for educational activities. The didactic activities suggested were based on the notes of Kamii & Jodeph (2005) and should be applied to students that are in the early years, regularly, methodical and gradual manner, aiming at the development of the necessary knowledge for mental calculation strategies.